CCL8 as a promising prognostic factor in diffuse large B-cell lymphoma via M2 macrophage interactions: A bioinformatic analysis of the tumor microenvironment - Lou, Xiaoli; Zhao, Ke; Xu, Jingze; Shuai, Lixiong; Niu, Hui; Cao, Zhifei; Wang, Juan; Zhang, Yongsheng (Frontiers in Immunology, 2022)
Backgrounds: Prior investigations of the tumor microenvironment (TME) of diffuse large B cell lymphoma (DLBCL) have shown that immune and stromal cells are key contributing factors to patients’ outcome. However, challenges remain in finding reliable prognostic biomarkers based on cell infiltration. In this study, we attempted to shed some light on C-C motif chemokine ligand 8 (CCL8) in DLBCL. Methods: Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data (ESTIMATE) algorithm was applied to evaluate immune and stromal scores from transcriptomic profiles of 443 DLBCL samples from The Cancer Genome Atlas (TCGA) and GSE10846 datasets. Immune cell infiltration (ICI) clusters and gene clusters were obtained based on different immune cell infiltration and immune-related differentially expressed genes (DEGs) of each sample. Hub genes were obtained by COX regression analysis and protein-protein interaction (PPI) network construction, then verified in the FFPE tissues. The Gene Oncology (GO), KEGG, and TIMER website were employed to explored the biological functions of CCL8-related DEGs. Cox regression analyses were performed to analyze CCL8 as independent prognostic risk factor, and was verified in other independent GEO cohorts. Results: Higher stromal score was associated with favorable prognosis in DLBCL. Patients in ICI B cluster and gene B clusters had better follow up status with higher programmed death ligand 1 (PD-L1) and Cytotoxic T - Lymphocyte Antigen 4 (CTLA4) expression. CCL8 and CD163 were identified as distinct prognosis association factors . Abundant M2 macrophages were discovered in the high-CCL8 expression group. CCL8 was an independent prognostic risk factor through COX regression analysis. Conclusions: CCL8 has been implicated in macrophage recruitment in several solid tumors, and only a few reports have been published on the role of CCL8 in the pathogenesis of hematological malignancies. This article attempted to find out TME-related genes that associated with the survival in DLBCL patients. CCL8 was identified to be involved in immune activities. Importantly, a series of bioinformatics analysis indicated that CCL8 might become an effective target for DLBCL in which interacting with M2 macrophage and immune check point. The potential related mechanisms need to be further elucidated.